The Relation of Soil Nutrients to the Incidence of Spike Disease in Sandalwood (Santalum album Linn.) - Iyengar, A. V. Varadaraja (Indian Forester, 1960)
Spike disease in sandal is grouped under virus diseases of plants. It is fatal to sandal. Although little is known of the nature of the virus, considerable information is available about its physiological and pathological effect on sandal, which is a root parasite feeding on other plants growing near it. Analysis of the different parts of the plant in health and disease in relation to the make up of the mineral nutrients therein and in relation to the availability of these in the respective soils are reported here. Gradients in respect of the major soil constituents in those plants are also presented. The immediate effect of the virus is traced to the defective functioning of the root-ends and haustoria in consequence of which, the intake of the inorganic nutrients is seriously affected and interfered with. A possible mechanism of the differential functioning of the rootends and of haustoria is indicated herein. It is found that the host plants supply the sandal only certain nutrients while the soil is the direct source for some others. In effect, lime alone seems to be directly correlated with the incidence and physiology of spike disease in sandal.